Literatur Review: The Effect of Earnings Management, Company Size, and Audit Opinion on Audit Delay - Astuti, Iis Putri; Kuntadi, Cris (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This article is to review and do research on the factors that influence audit delays, specifically earnings management, company size, and audit opinion. The objective of this literature review article is to determine the hypothesis of the influence between variables that can be used in further studies. The method was descriptive qualitative and library research. The results of this literature review article indicated that (1) earnings management has a positive impact on audit delay; (2) company size has a positive impact on audit delay; and (3) audit opinion has a negative effect on audit delay. These findings contribute to the study of literacy in relation to the causes of audit delay.